High-resolution FTIR imaging of colon tissues for elucidation of individual cellular and histopathological features. Issue 2 (9th November 2015) - Nallala, Jayakrupakar; Lloyd, Gavin Rhys; Shepherd, Neil; Stone, Nick
Abstract : Comparison of spectral-histopathological features of a colon tissue measured using a conventional (5.5 μm × 5.5 μm, left) and a high-magnification (1.1 μm × 1.1 μm, right) FTIR imaging system with respect to HE stained tissue (middle). Abstract : Novel technologies that could complement current histopathology based cancer diagnostic methods are under examination. In this endeavour mid-infrared spectroscopic imaging is a promising candidate that can provide valuable bio-molecular information from unstained cells and tissues in a rapid and a non-destructive manner. With this imaging technique, the biochemical information obtained from smaller areas of the tissues can be of clinical significance and hence the measured pixel size. Until recently it was difficult to obtain spectral data from pixels below around 5 microns square. High NA objectives have been utilised to reduce the ideal diffraction limit, enabling for the first time elucidation of subcellular features. In this context, the ability of high-resolution imaging, obtained using novel high-magnification optics retro-fitted onto a bench top FTIR imaging system, to characterise histopathological features in colonic tissues has been tested. Formalin fixed paraffin embedded colon tissues from three different pathologies were imaged directly using the conventional and the high-magnification imaging set-ups. To circumvent chemical de-paraffinization protocols, an extended multiplicative signal correction (EMSC) based electronic de-paraffinization was carried out on all the infrared images. Multivariate analysis of the high-magnification infrared imaging data showed a detailed information of the histological features of the colon tissue in comparison to conventional imaging. Furthermore, high-magnification imaging has enabled a label-free characterization of the mucin rich goblet cell features in an unprecedented manner. The current study demonstrates the applicability of high-magnification FTIR imaging to characterise complex tissues on a smaller scale that could be of clinical significance.